Mass spectrometry of crown ethers - (:unkn) unknown (KLUWER ACADEMIC PUBL, 1996)
The mass spectra of benzo-15-crown-5 and benzo-18-crown-6 were investigated by mass spectrometry with different inlet systems, such as direct introduction, gas chromatography and liquid chromatography inlets. Different ionisation methods such as electron impact, chemical ionisation, electron capture or negative ion chemical ionisation were also studied. The results and the specific problems encountered for this group of substances are discussed based on the spectra obtained.
Keywords: crown ethers; mass spectra; electron impact; chemical ionisation; negative ion chemical ionisation